Interviewer effects from a total survey error perspective - Olson, Kristen (Boca Raton : CRC Press, 2020)
"The book presents a comprehensive collection of state-of-the-art research on interviewer-administered survey data collection. Although many surveys are conducted using self-administered modes, interviewer-administered modes continue to be optimal for surveys that require high levels of participation, include difficult-to-survey populations, and collect biophysical data. Interviewers are responsible for locating sampled units, contacting sampled individuals and convincing them to cooperate, asking questions on a variety of topics, collecting other kinds of data, and providing data about respondents and the interview environment"--
Section I. History and OverviewChapter 1: The Past, Present, and Future of Research on Interviewer EffectsKristen Olson, Jennifer Dykema, Allyson Holbrook, Frauke Kreuter, Jolene D. Smyth, Brady T. West, Chapter 2: The Legacy of Charles CannellPeter V. Miller, Nancy A. Mathiowetz Section II: Training InterviewersChapter 3: General Interviewing Techniques: Developing Evidence-Based Practices for Standardized InterviewingNora Cate Schaeffer, Jennifer Dykema, Steve M. Coombs, and Rob K. Schultz, Lisa Holland and Margaret HudsonChapter 4: How to Conduct Effective Interviewer Training: A Meta-Analysis and Systematic ReviewJessica Daikeler, Michael BosnjakSection III: Managing and Monitoring Interviewers and the Survey ProcessChapter 5: Exploring the Mind of the Interviewer: Findings from Research with Interviewers to Improve the Survey ProcessRobin Kaplan and Erica YuChapter 6: Behavior Change Techniques for Reducing Interviewer Contributions to Total Survey ErrorBrad Edwards, Hanyu Sun, and Ryan HubbardChapter 7: Statistical Identification of Fraudulent Interviews in Surveys: Improving Interviewer ControlsSilvia Schwanhäuser, Joseph W. Sakshaug, Yuliya Kosyakova, Frauke KreuterChapter 8: Examining the Utility of Interviewer Observations on the Survey Response ProcessBrady T. West, Ting Yan, Frauke Kreuter, Michael Josten, Heather SchroederSection IV: Interviewer Effects and Interview Context and ModeChapter 9: Why do Interviewers Vary in Achieving Interview Privacy and Does Privacy Matter?Zeina N. Mneimneh, Julie A. de Jong, Yasmin A. AltwaijriChapter 10: Unintended Interviewer Bias in a Community-based Participatory Research Randomized Control Trial among American Indian YouthPatrick Habecker, Jerreed IvanichChapter 11: Virtual Interviewers, Social Identities, and Survey Measurement ErrorFrederick G. Conrad, Michael F. Schober, Daniel Nielsen, Heidi ReichertChapter 12: Differences in Interaction Quantity and Conversational Flow in CAPI and CATI InterviewsYfke Ongena and Marieke HaanChapter 13: Interacting with Interviewers in Voice and Text Interviews on SmartphonesMichael F. Schober, Frederick G. Conrad, Christopher Antoun, Alison W. Bowers, Andrew L. Hupp, H. Yanna YanSection V: Interviewers and NonresponseChapter 14: Explaining Interviewer Effects on Survey Unit Nonresponse: A Cross-Survey AnalysisDaniela Ackermann-Piek, Julie M. Korbmacher, Ulrich KriegerChapter 15: Comparing Two Methods for Managing Telephone Interview CasesJamie WescottChapter 16: Investigating the Use of Nurse Paradata in Understanding Nonresponse to Biological Data CollectionFiona Pashazadeh and Alexandru Cernat, Joseph W. SakshaugSection VI: Interview Pace and BehaviorsChapter 17: Exploring the Antecedents and Consequences of Interviewer Reading Speed (IRS) at the Question LevelAllyson L. Holbrook, Timothy P. Johnson, and Evgenia Kapousouz, Young Ik ChoChapter 18: Response Times as an Indicator of Data Quality: Associations with Question, Interviewer, and Respondent Characteristics in a Health Survey of Diverse RespondentsDana Garbarski, Jennifer Dykema, Nora Cate Schaeffer, and Dorothy Farrar EdwardsChapter 19: Accuracy and Utility of Using Paradata to Detect Question-Reading DeviationsJennifer Kelley, Chapter 20: What do Interviewers Learn? Changes in Interview Length and Interviewer Behaviors over the Field PeriodKristen Olson and Jolene D. Smyth, Section VII: Estimating Interviewer EffectsChapter 21: Modeling Interviewer Effects in the National Health Interview StudyJames Dahlhamer, Aaron Maitland, Benjamin Zablotsky, and Carla ZelayaChapter 22: A Comparison of Different Approaches to Examining Whether Interviewer Effects Tend to Vary Across Different Subgroups of RespondentsGeert Loosveldt and Celine WuytsChapter 23: Designing Studies for Comparing Interviewer Variance in Two Groups of Survey InterviewersBrady T. West
OCLC-licensed vendor bibliographic record.
Keywords: Interviewing; Social surveys; MATHEMATICS / Probability & Statistics / General